Air-stable Li3InCl6 electrolyte with high voltage compatibility for all-solid-state batteries. Issue 9 (28th August 2019) - Li, Xiaona; Liang, Jianwen; Luo, Jing; Norouzi Banis, Mohammad; Wang, Changhong; Li, Weihan; Deng, Sixu; Yu, Chuang; Zhao, Feipeng; Hu, Yongfeng; Sham, Tsun-Kong; Zhang, Li; et al.
Abstract : Ambient-air-stable Li3 InCl6 halide solid electrolyte, with high ionic conductivity of 1.49 × 10 −3 S cm −1 at 25 °C, delivers essential advantages over commercial sulfide-based solid electrolyte. Abstract : Most inorganic solid-state electrolytes (SSEs) suffer from incompatibility with oxide cathode materials and instability in ambient air, presenting major barriers for their application in high performance all-solid-state batteries (ASSLBs). Herein, we report a rationally designed halide-based Li3 InCl6 SSE with a high ionic conductivity of 1.49 × 10 −3 S cm −1 (25 °C). The Li3 InCl6 SSE is stable towards oxide cathode materials ( e.g., LiCoO2 ) without any interfacial treatment. By applying the Li3 InCl6 SSEs, significantly enhanced electrochemical performances are achieved in terms of capacity and durability. Experimental investigations reveal that the Li3 InCl6 can avoid side reactions between the SSEs and the oxide cathode materials and thus effectively improve the Li + migration across the interface. Moreover, Li3 InCl6 is highly stable in ambient air and possesses good ionic conductivity retention after a reheating process, further making it an attractive electrolyte for next-generation ASSLBs.